Digitization Of Pt Pertamina Mor Iv Semarang Archives - Anastasia Lipursari; Vitara Cinta Tria Hanifa (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Record management plays an important role in the continuity of a company, namely as a source of information and a center for company history. This provides benefits for research, consideration for decision-making, preparation of good work programs, and guidelines for carrying out work in the future. Records management activities in the office are increasingly dynamic along with the dynamics of organizational activities. Many office practitioners experience difficulties in managing records both conventionally and electronically. The purpose of this research is to determine the digitization of archives carried out by PT Pertamina MOR IV, namely by using computer technology. The research methods used are observation and interviews. The results of this research indicate that PT Pertamina MOR IV has used a combination of handling, namely manual archives and digital archives. Theoretically, digitizing archives should be done through a document scanning process. However, the process of digitizing archives at PT Pertamina MOR IV is carried out by entering data into a computer via the MS Excel program without scanning the documents first. The writer's suggestion for digitizing PT Pertamina MOR IV archives is through a document scanning process, to make it easier to manage and handle the archives. Some of the conveniences provided are easy to operate, attractive appearance, document search facility, data security, automatic retention, connecting to a computer, and enabling OCR facilities.